Indirect to direct band gap transition through order to disorder transformation of Cs2AgBiBr6via creating antisite defects for optoelectronic and photovoltaic applications. Issue 24 (20th May 2022) - Hadi, M. A.; Islam, Md. Nurul; Podder, Jiban
Abstract : The bandgap of Cs2 AgBiBr6 is tuned to a direct bandgap by the disordering of Ag + /Bi 3+ cations, creating antisite defects. The creation of antisite defects in the sublattice of double perovskites opens a new avenue for the design of photovoltaic and optoelectronic materials. Abstract : Non-toxic lead free inorganic metal halide cubic double perovskites have drawn a lot of attention for their commercial use in optoelectronic and photovoltaic devices. Here we have explored the structural, electronic, optical and mechanical properties of lead-free non-toxic inorganic metallic halide cubic double perovskite Cs2 AgBiBr6 in its ordered and disordered forms using first-principles density functional theory (DFT) to verify the suitability of its photovoltaic and optoelectronic applications. The indirect bandgap of Cs2 AgBiBr6 is tuned to a direct bandgap by changing it from an ordered to disordered system following the disordering of Ag + /Bi 3+ cations by creating antisite defects in its sublattice. In the disordered Cs2 AgBiBr6, the Bi 6p orbital modifies the conduction band significantly and leads to a shift the conduction band minimum (CBM) from L to Γ -point. Consequently, the system changes from indirect to direct band gap material. At the same time the band gap reduces significantly. The band gap of Cs2 AgBiBr6 decreases from 2.04 eV to 1.59 eV. The absorption edge towards the lower energy region and strong optical absorption in the visible to the UV region indicate that the disordered direct band gap material Cs2 AgBiBr6 is appropriate for use in solar cells and optoelectronic and energy harvesting devices. Dielectric function, reflectivity and refractive index of disordered direct band gap material Cs2 AgBiBr6 is favorable for its optoelectronic and photovoltaic applications. However, its stability and ductility favor its thin film fabrication. The creation of antisite defects in the sublattice of double perovskites opens a new avenue for the design of photovoltaic and optoelectronic materials.